Simulating education. The bureaucratisation of schooling as a production of the simulacra - Piotr Zamojski (Problemy Wczesnej Edukacji)
The argument presented in this article stems from the experience of being engaged in a debate with schoolteachers, who pointed to the bureaucratisation of schooling as their main concern. Taking their way of formulating this problem as a guidepost for my thinking I have made an attempt aiming at understanding the link between bureaucracy and schooling. Starting from Max Weber classical view, thanks to its critique made by Claude Lefort I try to interpret the bureaucratisation of schooling with reference to Jean Baurillard theory of simulation as the production of the simulacra.